THE IMPLEMENTATION OF THE NATIONAL DEFENSE GRAND DESIGN WITHIN THE FRAMEWORK OF BHINNEKA TUNGGAL IKA: BUILDING NATIONAL IDENTITY AWARENESS THROUGH STATE DEFENSE - Setiawan, I Gusti Ngurah Oka Putra; Wati, Asma; Efendy, A. Gusti (Jurnal Pertahanan dan Bela Negara, 2023)
This research discusses the concept of state defense, focusing on the younger generation currently facing moral decline due to a lack of understanding of the concept of state defense. This research aims to rebuild awareness of Indonesian identity among the public, especially the younger generation, by utilizing the concept of state defense as a central element implementing the Grand Design of state defense while integrating the values of Bhinneka Tunggal Ika. This research is conducted juridically normative or within the scope of legal dogmatics. Normative studies try to find the truth based on the scientific logic from the normative side. This research has revealed that the concept of state defense and the national defense grand design plays a central role in the effort to rekindle national identity awareness in Indonesia, particularly among the younger generation. Through understanding that national identity is the foundation of the country’s defense objectives, harmony between the national defense grand design and national Pancasila values, culture, and aspirations is the key to strengthening national unity. The results of this study emphasize the importance of ensuring that the national defense grand design is aligned with the values of Bhineka Tunggal Ika, promoting cultural diversity as an integral aspect of national identity, and engaging the younger generation through state defense programs and education that include Indonesian history and culture. This helps build future leaders who have a sense of love and loyalty towards their nation and country and ensures that Indonesia’s cultural heritage remains alive and thriving in the era of globalization.